Development of an instrumented bench to assess torque production during hiking in sailing - Chan, Andy Jun Hao (2019)
Generally, many researches that have been done on speed sailing focused on the relationship between moments induced during hiking and sailing performances. It is important to be able to quantify hiking moment values and gather information about the data such as the peak moment, forces and the increasing rate of the moment. However due to connections restrictions, the old set-up is unable to connect to conventional computers today. The main focus of this project is on the development and improvisation of an existing hiking bench setup so that the hiking moment can be quantified on land and the set-up is highly integrable with any laptops or computers today. The improvised version of the hiking bench was subjected to functional testing to determine its capability in measuring of the hiking moments simultaneously. This report presents firstly, some background information regarding the biomechanics of sailing, followed by a literature review to introduce and provide a basic understanding of the principles used in the design of the instrumentation. Subsequently, the design of the improvised set-up will be discussed, followed by some simple functionality tests that were conducted to ascertain the functionality of the setup. Finally, the report concludes with the possible developments and upgrades that can be attained in the future.